Anxiolytic Effect of Exogenous Ketone Supplementation Is Abolished by Adenosine A1 Receptor Inhibition in Wistar Albino Glaxo/Rijswijk Rats - Kovács, Zsolt; D'Agostino, Dominic P.; Ari, Csilla (Frontiers in Behavioral Neuroscience, 2018)
Anxiety disorders are one of the most common mental health problems worldwide, but the exact pathophysiology remains largely unknown. It has been demonstrated previously that administration of exogenous ketone supplement KSMCT (ketone salt/KS + medium chain triglyceride/MCT oil) by intragastric gavage for 7 days decreased the anxiety level in genetically absence epileptic Wistar Albino Glaxo/Rijswijk (WAG/Rij) rats. To investigate the potential role of the adenosinergic system in the pathomechanism of anxiety we tested whether the inhibition of adenosine A1 receptors (A1Rs) influence the anxiolytic effect of the exogenous ketone supplement. As A1Rs may mediate such an effect, in the present study we used a specific A1R antagonist, DPCPX (1,3-dipropyl-8-cyclopentylxanthine) to test whether it modulates the anxiolytic effect of sub-chronically (7 days) applied KSMCT in the previously tested animal model by using elevated plus maze (EPM) test. We administered KSMCT (2.5 g/kg/day) alone by intragastric gavage and in combination with intraperitoneally (i.p.) injected of DPCPX in two doses (lower: 0.15 mg/kg, higher: 0.25 mg/kg). Control groups represented i.p saline and water gavage with or without i.p. DPCPX administration (2.5g/kg/day). After treatments, the level of blood glucose and beta-hydroxybutyrate (βHB), as well as body weight were recorded. KSMCT alone significantly increased the time spent in the open arms and decreased the time spent in the closed arms, supporting our previous results. Injection of lower dose of DPCPX decreased, while higher dose of DPCPX abolished the effect of KSMCT administration on EPM. Blood βHB levels were significantly increased after administration of KSMCT, while DPCPX did not change the KSMCT induced increase in blood βHB levels. These results demonstrate that A1R inhibition modified (decreased) the anti-anxiety effect of KSMCT administration implying that the adenosinergic system, likely via A1Rs, may modulate the exogenous ketone supplement induced anxiolytic influence.